Military architecture in the Netherlands and her former colonies (1500-1800) - Ploeger, Jan (Scientia Militaria - South African Journal of Military Studies, 2012)
In this article we wish to consider the history of certain Dutch fortifications in theNetherlands, her former colonies and spheres of influence. Special attention will be given to the construction of our Castle and the engineers responsible for the design of South Africa's most important historical monument.Trading concerns such as the Dutch East India and West India Companies erected fortifications as the occasion demanded in their possessions and areas under their control. This was done out of purely military or also commercial considerations which they deemed necessary for the protection of their interests against internalor external threats of trading competition.